PEMBUATAN BUKU PROFIL PANTAI BARU - Sarastri Mumpuni (Asian Journal of Innovation and Entrepreneurship, 2013)
Ngentak Hamlet is a hamlet near the river Progo and southern sea so that beforeMerapi erupted majority of Hamlet Ngentak livelihood is sand miners. In 2010 tragedyvolcanoes befall the area of Mount Merapi in the area of Yogyakarta and Central Java isone plus side is the abundance of sand so that the sand in Progo decreased turnover andit resulted in many of Hamlet Ngentak who have no livelihood so that at the timeresidents took the initiative to open a new Beach tourist area. Until now, the NewTurkish stand and grow with tremendous potential. It was supported by the publicationusing the New Turkish media blog. But the lack of profile in the form of a hard copy ofthe attraction to make a manager experienced problems when required to do apresentation. From this, the authors try to provide solutions to make New TurkishProfile Books as one of the potential that exists in the hamlet village Ngentak PoncosariSrandakan Bantul. This activity aims to help managers in making presentations on NewBeach, and for the documentation of data that has not been documented so that when itis needed again still no reference to previous data. The stages of its activities includingsocialization plan to make New Turkish Profile Books, gathering and grouping the dataas needed, exposure result of making New Turkish Profile Books. With the profile ofbooks, people, especially the new coastal managers more easily in the presentation ofthe new beach, if indeed they are needed. Community especially coastal managers feelthat the book profiles and they are excited to be able to reproduce again and alwaysupdate the data in the profile book if there is a change that should be changed.